حصر وتوثيق النباتات البرية المأكولة في منطقة جبلة - الشيخ بسيمة; الشاطر زهير; اسبر رشا (Latakia University Journal -Biological Sciences Series, 2018)
The study was carried out in Jablah region- in the Syrian Coastal Zone in 2016-2017 and included 11 villages. It aimed to identify wild edible plants species in this area, and to evaluate the cultural significance of each plant using Cultural food significance index (CFSI). Data was gathered through interviews with 100 person from the local population. 96 species, which belong to 36 families were recorded. Asteraceae represented by the highest number of species (15), followed by Fabaceae (11) and Rosaceae (8). Cultural food significance index (CFSI) values ranged between 0.2-651. Portuloca oleracea, Eryngium creticum, Cichorium intybus, which are vegetables eaten raw or as salads, have very high cultural significance, While Malva silvistris was the most popular cooked vegetable and with high cultural significance. Whereas Rubus sanctus was the most popular fruit species, which belong to the moderate cultural significance values group. The study showed declining uses of some wild edible species that are: Capsella bursa-pastoris, Geranium rotundifolium, Lamium aplexicaule, Trifolium physodes, and Increased demand for other species that are: Orchis anatolica, Cephalanthera kurdica, Anacamptis pyramidalis. تمت الدراسة في منطقة جبلة في الساحل السوري، في عام2017-2016 ، وقد شملت 11 قرية. هدفت الدراسة إلى حصر وتوثيق النباتات البرية المأكولة في منطقة جبلة، وتقدير الأهمية الثقافية لكل نبات استخدام مؤشر الأهمية الثقافية (CFSI) "أهمية الدور الذي يلعبه النبات ضمن ثقافة معينة". جمعت البيانات عن النباتات من خلال إجراء مقابلات شخصية مع مئة شخص من السكان المحليين. تم تسجيل 96 نوعاً نباتياً مأكولاً، تنتمي إلى 36 فصيلة، كانت الفصيلة النجمية Asteraceae هي الأكثر حضوراً متمثلةً بـ 15 نوعاً نباتياً، تلتها الفصيلة البقولية Fabaceae متمثلةً بـ11 نوعاً، ثم الفصيلة الوردية Rosaceae التي تمثلت بـ 8 أنواع. تراوحت قيم مؤشرCFSI بين 0.2-651. كانت البقلةportuloca oleracea ، القرصعنة Eryngium creticum والهندباء البرية Cichorium intybus من الأنواع ذات الأهمية الثقافية العالية جداً، وهي خضار تؤكل نيئة أو كسلطات، ومن الخضار المطبوخة كانت الخبيزة الأكثر شعبية وعالية الأهمية الثقافية. وكان الديس من الفاكهة الأكثر شعبية وينتمي إلى مجموعة الأنواع ذات الأهمية الثقافية المتوسطة. أظهرت الدراسة أن بعض الأنواع البرية المأكولة لم تعد تستخدم وهي: ساق العصفورة Capsella bursa-pastoris، ساق الحجلةGeranium rotundifolium ، الكنيفوشة Lamium aplexicaule والنفلة Trifolium physodes، وعودة الطلب على بعض أنواع فصيلة السحلبيات Orchidae وهي: Orchis anatolica، Cephalanthera kurdica، Anacamptis pyramidalis.